Non-linear Transitions: An Intergenerational Longitudinal Study of Today's Young Women in Education and Work. (November 2019) - Walsh, Lucas; Keary, Anne; Gleeson, Joanne
Labour markets are characterized by uncertainty and youth transitions by change. This longitudinal study of three generations of Australian women from nine families suggests something more nuanced, featuring continuities and discontinuities threaded throughout the lives of daughters, mothers, grandmothers and aunts interviewed over three decades. Discussion focuses on the most recent generation of interviewees, following some of the threads of their testimonies back through previous generations of family to reveal similarities and some differences in their navigation of education and work. The findings suggest that the pathways of women today are more fluid but no more disrupted than previous generations, urging continued wider reflection on the concept of transition in youth studies and related relational, spatial and temporal dimensions of study and working life. Though problematic, the transitions metaphor still has meaning in the non-linear journeys of women as they navigate their ways from school to post-school life.